Optical, thermal and dielectric studies of silver-silica nanoparticles synthesized via sol-gel technique - Taib, Taifunisyam; Al-Bat’hia,, Souad A. M.; Johan, Mohd Rafie; Basirun, Wan Jefrey; Chin, Kim Ming; Chia, Chang Cherng; Tan, Jia Herng (Trans Tech Publications, 2016)
Silver-silica nanocomposites (Ag-SiO2NCs), with unique properties such as highly resonant particle plasmons, conductivity and potential applications in optics and various nanoelectronics are very attractive materials for sensing probes in biotechnology. Ag-SiO2NCs with various compositions were synthesized through sol-gel technique. The morphology, optical and thermal stability of the nanocomposite were investigated and was compared with pure sol-gel to determine the effects of the nanoparticles. Transmission electron microscopy (TEM) confirmed that SiO2 was encapsulated Ag with mean size of 30 nm. Uv-vis spectroscopy shows that the surface plasmon resonance (SPR) peak show Ag-SiO2 NCs were greatly reduce due to the SiO2 particles. The permittivity and refractive index were decreased as the composition of Ag was increased at composition of 60% silver. The real permittivity is negative along the visible region. The trend stability of Ag-SiO2NCs were increased with the increased amount of silver.